Infantile epileptic spasms syndrome as an initial presentation in infantile choroid plexus papilloma: A case report - Faliang Zhou; Yu Li; Lixue Shen; Hongxin Yao; Xinlin Hou (Frontiers Media S.A., 2022)
We present an interesting report of a 5-month-old infant with epileptic spasms and developmental delay who presented with non-isolated ventriculomegaly in utero and whose brain magnetic resonance imaging revealed right ventricular choroid plexus papilloma (CPP). The epileptic spasms persisted even with the use of antiepileptic therapies but was apparently cured after the removal of a CPP.